Literary Mythscapes in the Brothers Grimm’s Deutsche Sagen: A Comparative Study of Frau Holle’s Myth and Friulian “Benandantism” - Baruffa, Luca (2024)
This paper aims to investigate the significance of Brothers Grimm’s Deutsche Sagen as a valuable analytical tool for studying issues related to literature, history and customs across different cultures and epochs. The paper focuses on the nineteenth-century German nationalism, examined through the lens of anthropological and literary genre studies. Building on the methodological framework that stems from André Jolles’ considerations on the Sage as a literary genre, as well as from Duncan Bell’s concept of “mythscape,” the discussion will juxtapose the Germanic figure of Frau Holle, as depicted in the Grimmian collection of “legends” with the phenomenon here defined as “Benandantism.” As for the research material, in addition to the outlined methodological tools and the Grimms’ Sagen, the corpus includes studies on the inquisitorial reports concerning the “benandanti” as first collected by Carlo Ginzburg. Ultimately, the purpose of this comparison is to highlight similarities that could indicate the perpetuation, in both myths, of specific memetic processes inherent to their respective cultures, thereby laying the groundwork for further research in this area.
Keywords: Grimm, Jacob; Grimm, Wilhelm